EFFICACY OF EUPHORBIA TIRUCALLI (L.) TOWARDS MICROBICIDAL ACTIVITY AGAINST HUMAN PATHOGENS - S.H.K.R.PRASAD; N.L. SWAPNA; MADAN PRASAD (International Journal of Pharma and Bio Sciences, 2011)
The knowledge of plants as therapeutic agents is as old as disease, which in turn is as ancient as man himself. Since times immemorial plants have been in use to cure the human ailments. In traditional medicine, many plants have provided valuable clues for being used as potentially antiparasitic, antimalarial, leishmanicidal, antitumorous, fungicidal and antibacterial compounds. Still number of plants has yet to be screened for their potential as medicinal plants. In accordance with this information, antimicrobial activity of Euphorbia tirucalli (L.) was tested, which is commonly considered as medicinal plant. Extracts of the stem portions of the plant made in acetone, chloroform, hexane, methanol and petroleum ether were tested for antimicrobial activity against Bacillus megaterium, B. subtilis, Escherichia coli, Enterobacter faecalis, Proteus vulgaris, Pseudomonas aeruginosa, Staphylococcus aureus, Aspergillus niger, A. fumigatus and Candida albicans. The acetone extracts were effective against the test organisms.